Preparation of Papers for IFAC Conferences & Symposia: Computer Vision-enabled Human-Cyber-Physical Workstation for Proactive Ergonomic Risks Mitigation. Issue 1 (2021) - Ling, Shiquan; Guo, Daqiang; Yan, Danqi; Zhao, Xuefeng; Leng, Yuquan; Rong, Yiming; Huang, George Q.
Abstract: In production, poor ergonomic environments not only lead to increased workloads and health hazards for employees but also tend to reduce efficiency and quality. Recently, the human-cyber-physical (HCP) system has been proposed and widely studies to meet human capabilities and limitations. However, most existing frameworks are still not adaptive enough to integrate humans into a smart production environment due to a lack of real-time individual human factors digitalization. This research proposes an HCP workstation model for comprehensive assembly resources digitalization and autonomous interaction by CPS enabling technologies. Based on this, an adaptive control system has been developed for proactive ergonomic risk mitigation. Computer vision is deployed for real-time individual ergonomic evaluation and a prototype has been set up for functional validation.